1992
DOI: 10.1128/jvi.66.5.2792-2797.1992
|View full text |Cite
|
Sign up to set email alerts
|

Formation of heterotrimers between the membrane-integrated and the soluble glycoproteins of vesicular stomatitis virus leads to their intracellular cotransport

Abstract: BHK cells infected with vesicular stomatitis virus serotype Indiana generate intracellularly two different types of glycoproteins: the authentic membrane-integrated G protein ofvirions and a smaller soluble Gs protein lacking the transmembrane and cytoplasmic domains which is secreted into the growth medium. A Gsl protein species which is formed during or shortly after translation in the endoplasmic reticulum lumen is modified in the same way as the Gl protein by endoglycosidase H-sensitive oligosaccharides of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…For instance, the ORF2 product of EAV (G s protein) is retained in the ER in its monomeric state, whereas dimers become Endo H resistant and are selectively incorporated into virus particles (13). Heterotrimer formation between the authentic membrane-integrated G protein of vesicular stomatitis virus and the smaller soluble G s fraction is required for secretion of the latter into the growth medium (51). By using monomer-and oligomer-specific antibodies to influenza virus hemagglutinin, it was shown that monomers are restricted to the ER, whereas assembled molecules are able to reach distal points in the transport pathway (9).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ORF2 product of EAV (G s protein) is retained in the ER in its monomeric state, whereas dimers become Endo H resistant and are selectively incorporated into virus particles (13). Heterotrimer formation between the authentic membrane-integrated G protein of vesicular stomatitis virus and the smaller soluble G s fraction is required for secretion of the latter into the growth medium (51). By using monomer-and oligomer-specific antibodies to influenza virus hemagglutinin, it was shown that monomers are restricted to the ER, whereas assembled molecules are able to reach distal points in the transport pathway (9).…”
Section: Discussionmentioning
confidence: 99%
“…After visualization by fluorography the G protein (Mr = 70 kDa) was quantitated by densitometry and the average of duplicate experiments is shown by the bar graphs. The minor faster moving component is believed to represent the soluble (G S ) protein (Schmidt et al, 1992).…”
Section: Characterization and Quantitation Of The Free Polymannose Oligosaccharides Produced By Vsv Ts045-infected Cells At Permissive Anmentioning
confidence: 99%
“…The role of shed RABV-G during infection is unknown, but it may serve as a decoy for the immune system, as has been observed for other viruses (26)(27)(28). Furthermore, shed VSV-G has been reported to bind to full-length glycoprotein for uptake into cells (23) and injection of soluble RABV-G ectodomains into the brains of mice increases locomotion (29), a rabies symptom believed to facilitate transmission to new hosts.…”
Section: Fusion Loops Stabilize Full-length Rabv-g Pre-fusion Conformationmentioning
confidence: 99%
“…Challenges in developing longer lasting rabies vaccines include the lack of the quality and durability of the resulting neutralizing antibody response, and the lack of efficacy of most antibodies against other emerging and circulating lyssaviruses [22,23]. Monoclonal antibody RVA122 is the type of antibody desired from rabies immunization.…”
Section: Neutralizing Antibody Recognitionmentioning
confidence: 99%
See 1 more Smart Citation